Power of mentorship for recruitment and retainment of trauma staff - Kathryn Schaffer; Diane Wintz; Jennifer Hites; Laura Zgliniec; Miriah Boettcher (Trauma Surgery & Acute Care Open, 2025)
Introduction Healthcare teams throughout the nation noted workforce realignment during the COVID-19 pandemic, which impacted staff recruitment and retainment. The trauma team implemented a dedicated curriculum and multifaceted education in 2017 and amplified these efforts during the COVID-19 pandemic to ensure that nursing assistants assigned to trauma would continue to pursue their original career pathways.Methods Mentorship recipients were HealthCare Partners (HCPs), employees at nursing-assistant level assigned to the trauma room during their shifts. HCPs with a minimum of 6 months of experience in the general emergency department (ED) were eligible for this position. Data regarding each HCP’s tenure as well as post-HCP career was tracked from 2017 to 2023 and reviewed to understand retainment.Results There were 194 HCPs who worked in the ED full time during the 7 years. 90 HCPs were dedicated to trauma and received the trauma nursing curriculum (46%). More than 80% of the HCPs year-over-year retained their employment in the trauma position. Almost all HCPs (88/90; 98%) either went on to major healthcare or prehospital careers or continued to work in this same capacity in trauma to date.Conclusions Recruitment and retainment are realistic if the opportunity matches the needs or incites motivation in the employee. We have designed an effective mentorship plan that accomplishes both goals and could be replicated in any healthcare system.